2020
DOI: 10.1016/j.waojou.2020.100483
|View full text |Cite
|
Sign up to set email alerts
|

Linking cross-reactivity clusters of food and respiratory allergens in PAMD@ to asthma and duration of allergy

Abstract: Background Component resolved diagnosis, recently redefined as precision allergy medicine diagnosis — PAMD@, may help understanding allergic cross-reactivity patterns among polysensitized patients and their clinical implication. Objective We aimed to investigate similarities among allergens by empirically determining the occurrence of co-sensitization patterns and to relate them to clinical features, in particular to asthma. Methods A retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In line with our study, the importance of PR‐10 proteins and profilins was confirmed for PFS patients 27 . A Viennese study examining sensitization clusters highlighted a strong relationship between sensitizations to food and respiratory allergens 28 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our study, the importance of PR‐10 proteins and profilins was confirmed for PFS patients 27 . A Viennese study examining sensitization clusters highlighted a strong relationship between sensitizations to food and respiratory allergens 28 …”
Section: Discussionsupporting
confidence: 89%
“… 27 A Viennese study examining sensitization clusters highlighted a strong relationship between sensitizations to food and respiratory allergens. 28 Without any doubt, diagnosis of food allergy depends on clear clinical symptoms, while sIgE testing and positive SPTs only indicate sensitization. However, patients with food sensitization have a high risk of developing food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology around network analysis revealed previously unknown disease entities in the field of psychopathology 39 as well as disease characteristics in asthmatic patients following sensitization clustering. 40 , 41 Unlike UMAP, however, network analysis commonly uses force directed layouts, 42 which distort the true nature of higher dimensional datasets. 21 …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study performed in Vienna, revealed that sensitization to PR-10 allergen proteins in addition to Bermuda-timothy grass pollen clusters showed the highest association with asthma (odds ratio, 4.22 and 95% CI: 2.32-7.68) and duration of allergy [38].…”
Section: Precision Allergy Molecular Diagnosis In Epidemiological Stu...mentioning
confidence: 99%